2017
DOI: 10.1093/europace/eux052
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis of patients with life-threatening ventricular arrhythmias induced by coronary artery spasm

Abstract: Patients with life-threatening VAs secondary to CAS are at particularly high-risk for recurrence, especially when insufficient medical therapy is administered. Non-dihydropyridine CCBs are capable of suppressing episodes, whereas beta-blocker treatment is predictive of VAs. Ultimately, in spite of medical intervention, some patients exhibited arrhythmogenic events in the long-term, suggesting that ICD implantation may still be indicated for all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 13 publications
1
41
0
2
Order By: Relevance
“…Similarly, another study also demonstrated high risk of recurrent ventricular arrhythmias in patients with ASCA secondary to VSA despite medical therapy. Thus, ICD may be protective, especially in this high-risk group of patients with ASCA [7].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study also demonstrated high risk of recurrent ventricular arrhythmias in patients with ASCA secondary to VSA despite medical therapy. Thus, ICD may be protective, especially in this high-risk group of patients with ASCA [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, for some VSA patients, taking a CCB at the time of rising may be effective. In addition, we may add another vasodilator such as long-acting nitrates, nicorandil and other types of CCBs (dihydropyridine CCB vs non-dihydropyridine CCB)[ 12 ]. Finally, as shown in the present case reports, we must check whether the prescribed vasodilators are brand-name vasodilators or not.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the need for ICD in VSA patients with cardiac arrest has been one of the unsolved problems of coronary spasm[ 28 , 32 , 56 , 79 , 80 ]. Recently, Sueda et al[ 32 ] have summarized the results that appropriate ICD shocks were observed in 24.1% of VSA patients with aborted ICD.…”
Section: Uncertain or Unsolved Problems Regarding Coronary Spasmmentioning
confidence: 99%
“…Recently, Sueda et al[ 32 ] have summarized the results that appropriate ICD shocks were observed in 24.1% of VSA patients with aborted ICD. Rodríguez-Mañero et al[ 80 ] have shown that ICD was effective when insufficient medications were administered in VSA patients. In the clinical setting, whether sufficient medications without ICD can prevent such malignant arrhythmia due to coronary spasm is still undetermined.…”
Section: Uncertain or Unsolved Problems Regarding Coronary Spasmmentioning
confidence: 99%